SINTESIS DAN KARAKTERISASI METAL ORGANIC FRAMEWORKS La-NDC SERTA POTENSI APLIKASINYA SEBAGAI SENSOR SENYAWA BORAKS - Muhammad Akbar Chaniago; Sura Menda Ginting; Febrian Solikhin (ALOTROP, 2024)
This study aim is to synthesize and characterize metal organic frameworks La-NDC and determine the electronic response to borax (H3BO3) compounds. The method used to synthesize La-NDC MOFs is the solvothermal method with dimethylacetamide (DMA) as solvent. The research was conducted in the learning laboratory of FKIP UNIB and the Basic Science laboratory of FMIPA UNIB from April to June 2022. The synthesis stages of La-NDC MOFs consisted of six stages, namely preparation, mixing, heating and cooling, washing, drying and weighing. Yield results obtained as much as 70.77% and 63.85%. The results showed that La-NDC MOFs have been synthesized with a slightly yellowish white crystalline form. Characterization of La-NDC MOFs was carried out using FTIR, SEM and XRD methods. The results of FTIR characterization showed that Lanthanum metal ions had coordinated with NDC ligands to form a network of MOFs, XRD characterization results showed that La-NDC MOFs had good crystallinity and SEM characterization results showed that the morphology of La-NDC MOFs resembled irregular rocks with diameters ranging from 73 - 581 m. The analytes used for the response test were borax, benzene, toluene and formalin. The electronic response test of La-NDC MOFs was carried out using a UV-Vis spectrophotometer at a wavelength range of 200-800 nm. The results of the electronic response test on the sample of MOFs with borax show that La-NDC MOFs have no potential as sensors because they do not show specific electronic behavior towards borax